2015
DOI: 10.1371/journal.pone.0117954
|View full text |Cite
|
Sign up to set email alerts
|

A Remarkable Age-Related Increase in SIRT1 Protein Expression against Oxidative Stress in Elderly: SIRT1 Gene Variants and Longevity in Human

Abstract: Aging is defined as the accumulation of progressive organ dysfunction. Controlling the rate of aging by clarifying the complex pathways has a significant clinical importance. Nowadays, sirtuins have become famous molecules for slowing aging and decreasing age-related disorders. In the present study, we analyzed the SIRT1 gene polymorphisms (rs7895833 A>G, rs7069102 C>G and rs2273773 C>T) and its relation with levels of SIRT1, eNOS, PON-1, cholesterol, TAS, TOS, and OSI to demonstrate the association between ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
66
0
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 86 publications
(81 citation statements)
references
References 74 publications
9
66
0
6
Order By: Relevance
“…Currently, there are only few works in world literature on the direct relationship between polymorphisms and prolonged life. Recent reports by Kilica et al [18] indicated a significant increase in sirtuin levels in the elderly (73.5 ± 1.0, 56-92 years) and a correlation between the incidence of the rs7895833 polymorphism AG genotype in individuals from this group and the control group, where the mean age was 46.9 ± 0.5 years. This genotype occurred in 33.3% of children (control group), in 27.0% of adults (control group) and in 45.6% of the elderly (study group) (p = 0.014) [18].…”
Section: Ys K U Sj Amentioning
confidence: 53%
See 4 more Smart Citations
“…Currently, there are only few works in world literature on the direct relationship between polymorphisms and prolonged life. Recent reports by Kilica et al [18] indicated a significant increase in sirtuin levels in the elderly (73.5 ± 1.0, 56-92 years) and a correlation between the incidence of the rs7895833 polymorphism AG genotype in individuals from this group and the control group, where the mean age was 46.9 ± 0.5 years. This genotype occurred in 33.3% of children (control group), in 27.0% of adults (control group) and in 45.6% of the elderly (study group) (p = 0.014) [18].…”
Section: Ys K U Sj Amentioning
confidence: 53%
“…Therefore, currently, thanks to the rise of molecular biology, the importance of different variants of genes in the modification of ageing processes is increasingly pointed out as well as their impact on the prolongation of human life. One of the leading representatives is the SIRT1 gene, whose polymorphisms (rs7895833 A > G, rs2273773 C > T) are indirectly related to ageing by affecting cholesterol metabolism, body mass, obesity and atherosclerosis, as well as directly by causing cognitive impairment or increasing the amount and activity of sirtuins [18,21,22,23,24]. In our study, patients who had a BMI of 25 or more constituted the control group as scientific evidence indicates they live significantly shorter than those with a normal body mass.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations